Non-celiac gluten/wheat sensitivity (NCGS) - a currently undefined disorder without validated diagnostic criteria and of unknown prevalence - Reese, I.; Schaefer, C.; Kleine-Tebbe, J.; Ahrens, B.; Bachmann, O.; Ballmer-Weber, B.; Beyer, K.; Bischoff, S. C.; Blumchen, K.; Doelle, S.; Enck, P.; Enninger, A.; et al. (Allergologie, 2019)
Within the last decade, non-celiac gluten/ wheat sensitivity (NCGS) has been increasingly discussed not only in the media but also among medical specialties. The existence and the possible triggers of NCGS are controversial. Three international expert meetings which proposed recommendations for NCGS were not independently organized and only partially transparent regarding potential conflicts of interest of the participants. The present position statement reflects the following aspects about NCGS from an allergist's and nutritionist's point of view: (A) Validated diagnostic criteria and/or reliable biomarkers are still required. Currently, this condition is frequently self-diagnosed, of unknown prevalence and non-validated etiology. (B) Gluten has not been reliably identified as an elicitor of NCGS because of high nocebo and placebo effects. Double-blind, placebo-controlled provocation tests are of limited value for the diagnosis of NCGS and should be performed in a modified manner (changed relation of placebo and active substance). (C) Several confounders hamper the assessment of subjective symptoms during gluten-reduced or gluten-free diets. Depending on the selection of food items, e.g., an increased vegetable intake with soluble fibers, diets may induce physiological digestive effects and can modify gastrointestinal transit times independent from the avoidance of gluten. (D) A gluten-free diet is mandatory in celiac disease based on scientific evidence. However, a medically unjustified avoidance of gluten may bear potential disadvantages and risks. (E) Due to a lack of diagnostic criteria, a thorough differential diagnostic work-up is recommended when NCGS is suspected. This includes a careful patient history together with a food-intake and symptom diary, if necessary an allergy diagnostic workup and a reliable exclusion of celiac disease. We recommend such a structured procedure since a medically proven diagnosis is required before considering the avoidance of gluten
CRIS-Team WoS Importer:2019-03-15